2017
DOI: 10.1167/17.6.9
|View full text |Cite
|
Sign up to set email alerts
|

Age effects on saccadic adaptation: Evidence from different paradigms reveals specific vulnerabilities

Abstract: Saccadic eye movements provide an opportunity to study closely interwoven perceptual, motor, and cognitive changes during aging. Here, we investigated age effects on different mechanisms of saccadic plasticity. We compared age effects in two different adaptation paradigms that tap into low- and high-level adaptation processes. A total of 27 senior adults and 25 young adults participated in our experiments. In our first experiment, we elicited adaptation by a double-step paradigm, which is designed to trigger p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…Indeed, a few older participants complained that they recognized how they should have aimed on one trial (e.g., "to the right") but became confused on the next trial because the target was different and required aiming in a different direction (e.g., "up"). As age impacts working memory and processing speed (for review see Reuter-Lorenz and Sylvester, 2005) as well as the use of strategies in problem-solving (for review, see Lemaire, 2010), it is not surprising that older participants exhibited worse performance compared to younger adults (McNay and Willingham, 1998;Buch et al, 2003;Bock and Girgenrath, 2006;Seidler, 2006;Heuer and Hegele, 2008;Hegele and Heuer, 2013;Trewartha et al, 2014;Huang et al, 2017;Vandevoorde and Orban de Xivry, 2018;Wolpe et al, 2018). A link between spatial working memory and adaptation tasks has even been reported in younger healthy individuals (Anguera et al, 2010;Anguera et al, 2012;Christou et al, 2016), implying that in general performance during adaptation tasks may be influenced by visuospatial memory capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a few older participants complained that they recognized how they should have aimed on one trial (e.g., "to the right") but became confused on the next trial because the target was different and required aiming in a different direction (e.g., "up"). As age impacts working memory and processing speed (for review see Reuter-Lorenz and Sylvester, 2005) as well as the use of strategies in problem-solving (for review, see Lemaire, 2010), it is not surprising that older participants exhibited worse performance compared to younger adults (McNay and Willingham, 1998;Buch et al, 2003;Bock and Girgenrath, 2006;Seidler, 2006;Heuer and Hegele, 2008;Hegele and Heuer, 2013;Trewartha et al, 2014;Huang et al, 2017;Vandevoorde and Orban de Xivry, 2018;Wolpe et al, 2018). A link between spatial working memory and adaptation tasks has even been reported in younger healthy individuals (Anguera et al, 2010;Anguera et al, 2012;Christou et al, 2016), implying that in general performance during adaptation tasks may be influenced by visuospatial memory capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults have been consistently found to show higher dual task costs when they have to share attentional resources between a motor task and secondary cognitive demands (Doumas, Rapp, & Krampe, 2009;Huxhold, Li, Schmiedek, & Lindenberger, 2006;Lee, Wishart, & Murdoch, 2002;Lövdén, Schaefer, Pohlmeyer, & Lindenberger, 2008;Overvliet, Wagemans, & Krampe, 2013). Age-related changes in motor learning processes have been linked to memory resources (Anguera, Reuter-Lorenz, Willingham, & Seidler, 2010;Trewartha, Garcia, Wolpert, & Flanagan, 2014) and also to executive functions (Heuer & Hegele, 2014;Heuer, Hegele, & Sülzenbrück, 2011;Huang, Gegenfurtner, Schütz, & Billino, 2017;Huang, Hegele, & Billino, 2018). These findings suggest that cognitive resources represent a major modulator of sensorimotor control in old age.…”
Section: Introductionmentioning
confidence: 98%
“…Since participants were less aware of the gradual sensory mismatch, it was suggested that fewer learning strategies were required to solve the discrepancy, and so adaptation was less susceptible to age-related cognitive decline. Similarly, Huang et al ( 2017 ) showed that the adaptation of saccadic eye movements on a simple tracking task was similar for young and older adults, however adaptation was less pronounced for older adults when required to make a perceptual judgement about the target of the saccade; a process that requires executive strategies which are also more vulnerable to age-related cognitive decline. Furthermore, it has been demonstrated that, in line with the Bayesian learner model (Kording et al 2007 ), older adults’ predictions of the environment (i.e.…”
Section: Introductionmentioning
confidence: 91%
“…Accordingly, it has been proposed that cognitive processes (i.e. strategic control mechanisms) used to resolve the sensory conflict may decay with age, but internal models employed post-exposure to the sensory conflict may be resistant to ageing (Bock and Schneider 2002 ; Bock 2005 ; Bock and Girgenrath 2006 ; Heuer and Hegele 2008 ; Hegele and Heuer 2010 ; Anguera et al 2011 ; Langan and Seidler 2011 ; Huang et al 2017 ). In support, Buch et al ( 2003 ) showed similar adaptation for young and older adults when the sensory conflict was introduced gradually compared to an abrupt change (cf.…”
Section: Introductionmentioning
confidence: 99%